A prelimenary study : Malaysian women in human-computer interaction practices. - Mahmud, Murni; Hussein, Idyawati; Md Tap, Abu Osman (IIUM Press, 2011)
This paper reports the involvement of ivomen in the Information Comnlunication Technology (ICT) specifically in Human Computer Interaction (HCI) practices in Malaysia. The study aims to identify the ivomen in job proficiency, experience and as decision-maker in the ICT industry. The results indicate that women in ICT have a low avareness of the importance of HCI knoivledge in use and related job offered, therefore their contribution to the industry may be limited due to lack of understanding of some domain of knowledge